Efficacy of nebulised L-adrenaline with 3% hypertonic saline versus normal saline in bronchiolitis (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Bronchiolitis is one of the most common respiratory diseases requiring hospitalization. Nebulized epinephrine and salbutamol therapy has been used in different centres with varying results. Objective: The objective of the study was to compare the efficacy of nebulised adrenaline diluted with 3% hypertonic saline with nebulised adrenaline diluted with normal saline in bronchiolitis. Methods: Fifty three infants and young children with bronchiolitis, age ranging from 2 months to 2 years, presenting in the emergency department of Manikganj Sadar Hospital were enrolled in the study. After initial evaluation, patients were randomized to receive either nebulized adrenaline I .5 ml ( 1.5 mg) diluted with 2 ml of3% hypertonic saline (group I) ornebulised adrenaline 1.5 ml (1.5 mg) diluted with 2 ml of normal saline (group II). Patients were evaluated again 30 minutes after nebulization. Results: Twenty eight patients in the group I (hypertonic saline) and twenty five in groupII (normal saline) were included in the study. After nebulization, mean respiratory rate decreased from 63.7 to 48.1 (p